Answer:
The value of x is
.
Explanation:
Given expression is:
![(2)/(3)(x-2)=4x](https://img.qammunity.org/2022/formulas/mathematics/high-school/kgut2o6ewgidzz10u0uupohko3zfqnpy6b.png)
We have to solve this for x.
First we will multiply both sides of the equation by 3
![3*(2)/(3)(x-2)=4x*3](https://img.qammunity.org/2022/formulas/mathematics/high-school/1oemic19j0v5o7hwwzs8xk8xlm2mtljk43.png)
2(x-2) = 12x
2x-4=12x
Now we will be subtracting 2x from both sides of the equation
2x-2x-4=12x-2x
-4=10x
10x=-4
Dividing both sides by 10
![(10x)/(10)=(-4)/(10)\\\\x=(-2)/(5)](https://img.qammunity.org/2022/formulas/mathematics/high-school/yefi1mrdqcq8bkhw8q1kcn3ivuu5u7jyhw.png)
Hence,
The value of x is
.